Growing tiny eyes: How juvenile jumping spiders retain high visual performance in the face of size limitations and developmental constraints. (July 2019) - Goté, John T.; Butler, Patrick M.; Zurek, Daniel B.; Buschbeck, Elke K.; Morehouse, Nathan I.
Highlights: Juvenile spider eyes are proportionally larger than their adult counterparts. Despite ontogenetic growth in eye size, photoreceptor numbers remain constant. Rhabdom volume and sensitivity increase in anterior lateral eyes across development. Field-of-view and acuity are maintained across development in anterior lateral eyes. Abstract: Adult jumping spiders are known for their extraordinary eyesight and complex, visually guided behaviors, including elaborate communicatory displays, navigational abilities, and prey-specific predatory strategies. Juvenile spiders also exhibit many of these behaviors, yet their visual systems are many times smaller. How do juveniles retain high visually guided performance despite severe size constraints on their visual systems? We investigated developmental changes in eye morphology and visual function in the jumping spider Phidippus audax using morphology, histology, ophthalmoscopy, and optical measurements. We find that juvenile spiders have proportionally larger lenses in relation to their body size than adults. This should alleviate some of the costs of small body size on visual function. However, photoreceptor number in the anterior lateral eyes (ALE) remains constant from early development onward, consistent with a developmental constraint on photoreceptor differentiation. To accommodate these photoreceptors within the diminutive volume of the spiderling cephalothorax, ALE rhabdoms in early life stages are more tightly packed and significantly smaller in diameter and length, properties that expand across development. Lens focal lengths increase as eyes and retinas grow, resulting in a remarkable maintenance of ALE spatial acuity and field-of-view across life stages. However, this maintenance of acuity comes at a sensitivity cost given the small rhabdomal volumes required by space constraints early in life. Taken together, our results indicate that young jumping spiders have eyes already equipped for high acuity vision, but these young spiders may struggle to perform visually demanding behaviors in low-light environments, a notion that warrants further testing.